The Challenges of Teaching the Revised English Syllabus - Judith, Gathua; Gladys, Kiptiony; Antony, Somba (KABARAK UNIVERSITY, 2012)
The research is an assessment of the multifaceted role that English plays as a medium of interaction/ instruction or service subject, a compulsory discipline at all levels of education and as the official language of the republic of Kenya. As a medium of instruction, English services the teaching of all other disciplines of the curriculum. Though a third or even fourth language to learners of English it is used for interaction between teachers and learners and amongst the learners themselves. English is also an examinable discipline at different summative levels in the education system. It is also a major tool used to achieve both the curriculum goals of education and the national goals enshrined in vision 2030. The research will attempt to address the apparent gap in the interpretation, implementation and the evaluation of the revised syllabus. The main objective will be to determine the extent to which the mandate of the teacher, in the teaching of English meets the needs of the learners of English in Kenyan secondary schools. The research design will take on a quantitative approach using questionnaires administered to respondents from secondary schools in Nakuru County. Random sampling technique will be used to pick out a broad spectrum of respondents. The findings will inform curriculum developers and the ministry of education the challenges that the teacher is grappling with in preparing learners to acquire English as a foreign language and the bearing this has on learners of English.
Keywords: English Syllabus; Challenges of Teaching